Association of GLP1R variants rs2268641 and rs6923761 with obesity and other metabolic parameters in a Polish cohort - Michałowska, Joanna; Miller-Kasprzak, Ewa; Seraszek-Jaros, Agnieszka; Mostowska, Adrianna; Bogdański, Paweł (Frontiers in Endocrinology, 2022)
Introduction: Obesity is a complex disease associated with excessive fat accumulation and numerous metabolic complications. So far, many factors leading to the development of this disorder have been identified, including genetic susceptibility. Various studies linked GLP1R variants with anthropometric and metabolic parameters, suggesting the role of the variation in this gene in metabolic health. Objective: The aim of this study is to investigate the association of two single nucleotide variants of GLP1R gene, rs2268641 and rs6923761, with excessive weight, metabolic syndrome, anthropometric measurements and selected metabolic parameters. Methods: Normal-weight subjects (n= 340, control group) and subjects with excessive body mass (n = 600, study group) participated in this study. For all participants, anthropometric measurements and metabolic parameters were collected, and genotyping of the two single nucleotide variants of GLP1R gene, rs2268641 and rs6923761, was performed using the high-resolution melting curve analysis. Results: Significant differences in the genotype distribution of rs2268641 were found, where homozygous TT genotype was significantly less frequent in the study group with excessive body mass (OR=0.66; p=0.0298). For rs6923761, A allele and homozygous AA genotype were significantly more frequent in the study group with excessive weight than in the control group (OR=1.27; p=0.0239 and OR=1.69; p=0.0205, respectively). The association of studied variants with metabolic parameters was found for rs6923761. For this variant, AA carriers had higher body mass in comparison to GG carriers (p=0.0246), and AA carriers had higher glucose concentration in comparison to AG carriers (p=0.0498). We did not find an association of rs2268641 and rs6923761with metabolic syndrome. Conclusion: In our study, AA carriers of rs6923761 had higher risk of excessive body mass, whereas TT carriers of rs2268641 had lower risk of being overweight. Moreover, homozygous carriers of the minor allele of rs6923761 had higher glucose concentration in comparison to heterozygous subjects. None of the studied variants were associated with metabolic syndrome in the studied population.